Fate of the Late Triassic Songpan-Ganzi Basin in the eastern Paleo-Tethys Ocean: Geochemical and geochronological constraints in the NE Tibetan Plateau - Hong-Xu Mu; Dan-Ping Yan; Liang Qiu; Ruo-Yan Kong; Ling-Xiao Gong (Journal of Asian Earth Sciences: X)
The Songpan-Ganzi Basin in the northeastern Tibetan Plateau preserves well-developed Late Triassic flysch sequences, making it an ideal region for investigating the provenance and tectonic evolution of the basin. This study aimed to constrain the provenance and tectonic setting of the basin by analyzing whole-rock geochemistry and detrital zircon U-Pb ages from Late Triassic flysch sediments. The flysch sequences show low SiO2 (average 51.16 wt%), Al2O3 (average 9.85 wt%) and Fe2O3T + MgO (average 6.56 wt%) values, and K2O/Na2O (average 2.71) ratios, along with high SiO2/Al2O3 ratios (averaging 6.99), suggesting a continental arc setting. They also exhibit moderate chemical weathering (CIA: 60.32–83.72) and high component variability (0.9–2.34, average 1.61), revealing a moderately weathered source. Tectonic discrimination diagrams based on La-Sc-Th and Th-Sc-Zr/10 ratios suggest a continental arc setting. U-Pb ages of detrital zircons mainly range from 222 to 300 Ma and 450 to 520 Ma, reflecting the time of the emplacement of Paleozoic to Late Triassic plutons in the Qinling orogenic belt and Kunlun arc. Minor age peaks (720–850 Ma, 950–1300 Ma and 1400–2400 Ma) suggest subordinate contribution from the northern and western margins of the Yangtze Block. Cumulative proportion curves of zircon U-Pb ages for lower formations exhibit a steep accumulation trend, suggesting a convergent tectonic setting. In contrast, upper formations display a relatively flat accumulation curve, indicative of a collisional environment. This shift in curve characteristics suggests that the sedimentary environment evolved from convergent to collisional settings among the North China, South China, and Qiangtang blocks.